2009
DOI: 10.4028/www.scientific.net/kem.405-406.343
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Flexural Performance of Corroded RC Beams Strengthened with AFRP Sheets

Abstract: In order to investigate the strengthening effects of aramid fiber reinforced polymer (AFRP) sheets on the flexural performance of the corroded beams, the flexural behaviors of corroded RC beams strengthened with AFRP sheets under different degrees of corrosion (minor: reinforcement mass loss is 2.0%, medium: reinforcement mass loss is 6.0%) are researched experimentally in this paper, and compared with that of the control beams (un-corroded) and un-strengthened corroded beams. The results show that,compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…Kashi et al [ 24 ] investigated the effect of marine environmental conditions on the durability of RC corroded columns strengthened with FRP sheets. Some researchers also investigated the structure performance of AFRP-strengthened corroded RC beams [ 25 , 26 ]. Gotame.…”
Section: Introductionmentioning
confidence: 99%
“…Kashi et al [ 24 ] investigated the effect of marine environmental conditions on the durability of RC corroded columns strengthened with FRP sheets. Some researchers also investigated the structure performance of AFRP-strengthened corroded RC beams [ 25 , 26 ]. Gotame.…”
Section: Introductionmentioning
confidence: 99%
“…Zongcai Deng et al [ 15 ] demonstrated that using carbon/aramid/glass interlayer hybrid fiber cloth reinforcement can effectively improve the bending performance of corroded beams. Wei et al [ 16 ] studied the performance of CFRP cloth, GFRP cloth, and other fiber layer hybrid bonding to reinforce reinforced concrete beams. Research has found that the higher the ultimate tensile strength and distribution of fiber materials, the more significant the improvement in the ultimate bearing capacity of the test beam.…”
Section: Introductionmentioning
confidence: 99%
“…Εναλλακτικά, οι Deng et al (2009) χρησιμοποίησαν σύνθετα υλικά ινών αραμιδίου (AFRP) για την ενίσχυση διαβρωμένων δοκών σε διαφορετικά επίπεδα απώλειας μάζας του οπλισμού και κατέληξαν ότι τα υφάσματα ινών αραμιδίου μπορούν να βελτιώσουν σημαντικά την καμπτική αντοχή και τις βυθίσεις δοκών ακόμα και με υψηλό βαθμό διάβρωσης σε σύγκριση με μικρότερους βαθμούς διάβρωσης. Οι El Maaddawy et al ( 2013) μελέτησαν την επιρροή της έκθεσης σε συνθήκες διάβρωσης δοκών ενισχυμένων καμπτικά με ελάσματα FRP και μεταλλικούς σφιγκτήρες (Powder Actuated Fastened PAF).…”
Section: 6unclassified